IKAN GARING (GENUS: Tor) SEBAGAI MODEL PENELITIAN HISTOLOGI IKAN AIR TAWAR: LITERATUR REVIEW - Gabriella Jessica Agatha; Aulia Devani Putri; Sandi Fransisco Pratama (Jurnal Biogenerasi, 2026)
Histological analysis is a fundamental approach for understanding tissue structure and biological responses of freshwater fish to environmental and physiological conditions. The selection of an appropriate model organism is crucial to ensure accurate interpretation of histological findings. This literature review aims to evaluate the potential of freshwater fish from the genus Tor as a model organism for histological research. Secondary data were obtained from national and international scientific articles published between 2016 and 2024 that discuss histological and histopathological studies of freshwater fish, with a specific focus on genus Tor. Literature searches were conducted using Google Scholar, Garuda, and PubMed with relevant keywords. A total of five relevant articles were selected based on predefined inclusion criteria and analyzed descriptively by comparing the organs examined, histological approaches applied, and major findings related to tissue structure. The reviewed studies indicate that histological investigations on Tor species have covered various organs, including gills, liver, digestive tract, muscle tissue, and larval structures. The results consistently demonstrate that tissue structures in genus Tor are clearly observable and responsive to environmental changes, physiological conditions, and developmental stages. Therefore, genus Tor shows strong potential as a model organism for freshwater fish histological studies, particularly in biomonitoring, environmental assessment, and fish health evaluation.